2009
DOI: 10.1007/s00586-009-1055-0
|View full text |Cite
|
Sign up to set email alerts
|

Onset of a Charcot spinal arthropathy at a level lacking surgical arthrodesis in a paraplegic patient with traumatic cord injury

Abstract: The study design included a case report of Charcot spinal arthropathy treated with posterior and anterior spinal instrumentation. The objective of the study was to report an unusual case of Charcot spinal arthropathy as a late complication of traumatic spinal cord injury in a patient previously treated with a long posterior thoracolumbar instrumentation and postero-lateral fusion. A 33-year-old man with T10-T11 complete paraplegia presented with focal low back pain, kyphotic deformity of the lumbar region with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Nevertheless, complications represent undesirable consequences of lumbar spine surgery in adult patients. Patients’ age, medical comorbidities and fusion extending up to the sacrum are identified as predisposing risk factors 123456. The development of new guidelines in perioperative nutrition, pulmonary management and intraoperative neuromonitoring have been considered important measures in decreasing the complication rate 78.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, complications represent undesirable consequences of lumbar spine surgery in adult patients. Patients’ age, medical comorbidities and fusion extending up to the sacrum are identified as predisposing risk factors 123456. The development of new guidelines in perioperative nutrition, pulmonary management and intraoperative neuromonitoring have been considered important measures in decreasing the complication rate 78.…”
Section: Introductionmentioning
confidence: 99%
“…Other orthopedic surgeons may have preferred circumferential fusion of the spine. 7,10,12 But the surgical interven-tion decided upon for our patient seemed to be the most adapted to the circumstances.…”
Section: Discussionmentioning
confidence: 92%
“…Surgical options considered with CSA include anterior and posterior circumferential fusion with extensive anterior debridement, posterior instrumentation, and autogenous bone graft. Posterior fixation allows mechanical stability, while biological secondary stability is dependent on bone fusion [8]. In a four-case review, no serious post-operative complication or instrumentation failure was observed [9].…”
Section: Discussionmentioning
confidence: 95%